1991
DOI: 10.1113/jphysiol.1991.sp018547
|View full text |Cite
|
Sign up to set email alerts
|

Shortening of muscle fibres during stretch of the active cat medial gastrocnemius muscle: the role of tendon compliance.

Abstract: SUMMARY1. The length of muscle fibres in the medial gastrocnemius (MG) muscle of the anaesthetized cat was measured using ultrasound techniques. During the course of 'isometric' contractions, the muscle fibres shortened by stretching the compliant tendons, until the muscle fibres could no longer produce enough force to stretch the tendons further. At optimal muscle length (L.) the maximal shortening of muscle fibres was 28%.2. At muscle lengths much longer than L., 'isometric' contractions produced a slow shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
266
7
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(289 citation statements)
references
References 28 publications
15
266
7
1
Order By: Relevance
“…The vast majority of muscle fascicle lengthening happened later in the event, when there was relatively little joint flexion. This decoupling of joint motion and muscle fascicle lengthening during an energy-absorption event has been observed in maximally stimulated muscles in situ [14,16], and in maximal voluntary contractions in human dynamometer studies [15]. A recent study of stair walking found a similar pattern in the human gastrocnemius: the muscle fascicles shortened early in the step as the MTU lengthened, followed by tendon shortening against lengthening of the muscle fascicles [28].…”
Section: Discussionmentioning
confidence: 71%
“…The vast majority of muscle fascicle lengthening happened later in the event, when there was relatively little joint flexion. This decoupling of joint motion and muscle fascicle lengthening during an energy-absorption event has been observed in maximally stimulated muscles in situ [14,16], and in maximal voluntary contractions in human dynamometer studies [15]. A recent study of stair walking found a similar pattern in the human gastrocnemius: the muscle fascicles shortened early in the step as the MTU lengthened, followed by tendon shortening against lengthening of the muscle fascicles [28].…”
Section: Discussionmentioning
confidence: 71%
“…slightly so that spindles 'see' slightly less of the origin-toinsertion length (Hoffer et al 1989;Elek, Prochazka, Hulliger & Vincent, 1990;Griffiths, 1991). At the end of the stance phase, the tendon is unloaded and therefore shortens slightly, adding a small component of length to the spindles that is not registered by the length transducer.…”
Section: Figure 1 Illustration Of Averaging Techniquementioning
confidence: 99%
“…In addition, the potential tendon elongation may act as a mechanical buffer limiting the amount of fascicle lengthening and muscle injury from eccentric muscle action. 12,23 The intensity of the activity may also affect the length of the VL fascicle. As the intensity of the drop jump increases, the fascicle lengthens less during the braking or knee flexion phase.…”
Section: Vastus Lateralismentioning
confidence: 99%